The Text of II Samuel 7,13 and the Redaction of Nathan’s Oracle - Willis, Timothy M. (Zeitschrift für die alttestamentliche Wissenschaft, 2021)
The dtr. nature of II Sam 7,13a is a crucial piece in reconstructions of the redactional history of Nathan’s dynastic oracle. The present study argues that the parallel account in I Chr 17,12a preserves the earliest reading. A later copyist revised II Sam 7,13 to align the verse with corresponding clauses in I Chr 22,10.